PENGARUH PEMBERIAN INSENTIF TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PT PETROKOPINDO CIPTA SELARAS GRESIK - Suhardi, Suhardi (Fakultas Ekonomi Universitas Gresik, 2012)
Human resources are the labor force that is used to achieve optimal results in their work, meaning the output will be better achieved. Disarnping that when the ability of the dirniliki by an employee who can be taught to other labor and if it went well then the company will be able to more quickly growing.Relative to employee productivity problems: the problem of absenteeism has a huge inÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã‚Â¡uence. It also reÃƒÆ’Ã†â€™Ãƒâ€šÃ‚Â¯ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â¬ÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬Ãƒâ€¦Ã‚Â¡ects the compliance / discipline of the employee, if an employee is absent continuously so that should receive the serious attention of the company, because if it is allowed will affect the morale of other employees who had always dutifully come to be undisciplined. Many ways by which companies to motivate employees to show better work than before, motivating tool is one of them is an incentive, the incentive is in addition to the revenue earned by the employee sebagar reward for work performance dicapainya.Tujuan this study was to determine whether the incentives have an effect on productivity and related work on PT Gresik Petrokopindo Copyright harmony.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â